A bidentate halogen-bonding bromoimidazoliophane receptor for bromide ion recognition in aqueous media. - Caballero, A; White, N; Beer, P (2011)
A bidentate halogen-bonding bromoimidazoliophane receptor selectively binds bromide ions in competitive aqueous media (see picture, gray=carbon, blue=nitrogen, brown=bromine). The bromide ions are bound by cooperative convergent bromine atom/halogen-bonding halide anion interactions. © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.